To believe or not to believe - E.D. Klemke
A comprehensive anthology of selections for the Introductory Philosophy of Religion course, this text surveys more than 50 responses to the question, "Is religious belief a viable option in today's world?" Organizes selections around central theistic positions and attacks on those positions. Pro-con format encourages lively discussions